Transient and relict landforms in a lithologically heterogeneous post-orogenic landscape in the intertropical belt (Alto Paranaíba region, Brazil) - Marques, Karina P.P.; dos Santos, Marcilene [UNESP]; Peifer, Daniel; da Silva, Clauzionor Lima; Vidal-Torrado, Pablo (Elsevier, 2021)
High elevations and steep slopes are currently observed in ancient mountain ranges despite active tectonics having ceased tens to hundreds of millions of years ago. Explanations for landscape dynamics in these settings generally postulate that post-orogenic relief is either the product of a recent topographic rejuvenation episode (or episodes) or was formed by ancient orogenesis after which the landscape has survived ever since, perhaps in a topographic equilibrium condition where erosion is spatially uniform. Here, we explore the morphology of a tropical wet and dry, high relief post-orogenic landscape in the Brazilian continental interior capped by ferruginous duricrusts and characterised by stark lithological variability. We explore whether a decline in relief has remained constant or increased during its post-orogenic evolution. We show that river knickpoints demarcate regional topographic transitions between 1) flat, relict uplands, 2) a rugged transition zone where channels and adjacent hillslopes are steep, and 3) gentle lowland morphologies in downstream areas. Relict areas are primarily capped by ferruginous duricrusts that are likely Eocene, as suggested by weathering geochronology in surrounding areas. Topography in the study area records at least two regional, transient topographic disequilibrium events, where the oldest drop in relative base level is expressed by knickpoints lying in high elevations fixed within ferruginous duricrusts that slow the propagation of the transient base level lowering signal. This transience is consistent with regional uplift events, likely driven by denudational isostatic rebound or compressional far-field stresses, with local effects superimposed linked with the strike-slip reactivation of old faults and the formation of the Pratinha Pull-Apart Basin. Relief is growing as the topography is slowly decaying, yet the topographic configuration of the area was established before these disequilibrium events. Our study demonstrates that ancient and younger landforms coexist in a post-orogenic setting, implying that the competing hypotheses for post-orogenic development are not mutually exclusive.
Keywords: Ferruginous duricrust; Knickpoints; Quantitative geomorphology; Topographic rejuvenation